Pre- and Neonatal Imprinting on Immunological Homeostasis and Epithelial Barrier Integrity by Escherichia coli Nissle 1917 Prevents Allergic Poly-Sensitization in Mice - Sarate, Priya J.; Srutkova, Dagmar; Geissler, Nora; Schwarzer, Martin; Schabussova, Irma; Inic-Kanada, Aleksandra; Kozakova, Hana; Wiedermann, Ursula (Frontiers in Immunology, 2021)
A steady rise in the number of poly-sensitized patients has increased the demand for effective prophylactic strategies against multi-sensitivities. Probiotic bacteria have been successfully used in clinics and experimental models to prevent allergic mono-sensitization. In the present study, we have investigated whether probiotic bacteria could prevent poly-sensitization by imprinting on the immune system early in life. We used two recombinant variants of probiotic Escherichia coli Nissle 1917 (EcN): one expressing birch and grass pollen, poly-allergen chimera construct (EcN-Chim), and ii) an "empty" EcN without allergen expression (EcN-Ctrl). Conventional mice (CV) were treated with either EcN-Chim or EcN-Ctrl in the last week of the gestation and lactation period. Gnotobiotic mice received one oral dose of either EcN-Chim or EcN-Ctrl before mating. The offspring from both models underwent systemic allergic poly-sensitization and intranasal challenge with birch and grass pollen allergens (Bet v 1, Phl p 1, and Phl p 5). In the CV setting, the colonization of offspring via the treatment of mothers reduced allergic airway inflammation (AAI) in offspring compared to poly-sensitized controls. Similarly, in a gnotobiotic model, AAI was reduced in EcN-Chim and EcN-Ctrl mono-colonized offspring. However, allergy prevention was more pronounced in the EcN-Ctrl mono-colonized offspring as compared to EcN-Chim. Mono-colonization with EcN-Ctrl was associated with a shift towards mixed Th1/Treg immune responses, increased expression of TLR2 and TLR4 in the lung, and maintained levels of zonulin-1 in lung epithelial cells as compared to GF poly-sensitized and EcN-Chim mono-colonized mice. This study is the first one to establish the model of allergic poly-sensitization in gnotobiotic mice. Using two different settings, gnotobiotic and conventional mice, we demonstrated that an early life intervention with the EcN without expressing an allergen is a powerful strategy to prevent poly-sensitization later in life.